Trading between Architecture and Art. - Davidts, Wouter; Dorrian, Mark; Holden, Susan; Campens, Angelique; Linder, Mark; Walker, Stephen; Willink, Rosemary; Vervoort, Stefaan; Paine, Ashley (Amsterdam : Valiz, 2019)
Körmeling, John ; Assemble ; Metten, Philip ; Kiesler, Frederick ; Moeschal, Jacques ; Richter, Gerhard ; The Met Breuer, Rotor
Wisselwerking tussen kunst en architectuur sinds 1960
boek